Detecting Defects in Multicomponent Software Using a Set of Universal Graph Representations of the Code - Kubrin, G. S.; Zegzhda, D. P. (Automatic control and computer sciences, 2024)
A comparison of the existing software analysis methods is presented with an assessment of the possibility of identifying defects contained in several components implemented in different programming languages. A set of three universal graph representations of code is proposed for implementing security analysis methods that take into account interactions between software components using different sets of programming languages. For the proposed universal code representations, a concept of a security analysis system and a prototype of the system implementation are developed, supporting cross-language analysis of the software components implemented in the programming languages PHP and C, as well languages using the .NET platform.